Changes in the muscle mass by population group: findings on the PERU MIGRANT cohort study - Arriarán-García, Jassira S. (2025)
Objectives: Muscle mass decline is common among adults, and in certain groups, it may occur earlier. This study evaluated the change in skeletal muscle mass (SMM) and relative skeletal muscle mass (RSMM) in three population groups (rural, rural-to-urban migrant, and urban). Materials and methods: Secondary analysis of the PERU MIGRANT study, a cohort with 8 years of follow-up. SMM was assessed using the Lee equation, and RSMM was determined by dividing SMM by body weight, whereas the exposure was the population group. The change in MME and MMER in the three groups of interest was assessed using linear mixed models, and coefficients (β) and 95% confidence intervals (95% CI) were reported. Results: A total of 989 subjects (rural: 201, migrant: 589, and urban: 199) were analyzed, with a mean age 48.0 (SD: 12.0) and 522 (52.8%) women. At baseline of the cohort, SMM was higher in urban dwellers than in migrants and rural; while RSMM was lower in urban compared to migrants and rural populations. After eight years of follow-up, SMM decreased in urban (β=-0.47; 95% CI: -0.77 to -0.18) and migrants (β=- 0.36; 95% CI: -0.57 to -0.15) groups, but not among rural (β=0.07; 95% CI: -0.10 to 0.24) dwellers. On the other hand, RSMM increased in urban (β=0.50; 95% CI: 0.30 to 0.71) and migrants (β=0.34; 95% CI: 0.18 to 0.49) populations, but it decreased markedly in rural dwellers (β=-2.12; 95% CI: -2.25 to -1.99). Conclusions: In our study, MME and MMER varied differently according to the population group (rural, migrants, and urban).